DIGITAL TECHNOLOGIES IN TEACHING CONDUCTING: Received: 24th November 2022; Revised: 18th January 2023, 20th January 2023; Accepted: 24th January 2023 - Rosiński, Adam (PUPIL: International Journal of Teaching, Education and Learning, 2023)
The objective of this paper was to invent a digital technology, that could be used in a simple way in online conducting classes, throughout specialized education of students at universities. Transition to remote teaching due to Covid-19 pandemic has highlighted the gap in this field. This article presents a concept of using a specialised software, that is mapping in a 3D space and analysing the movement of human body in real time. The software combines two images provided by the cameras installed in a smartphone and a computer. Common presence of laptops and smartphones in human life makes it possible to omit the costs of buying specialised equipment. The technology was researched with professors and students involved, to verify: software stability, level of detail in the rendered movements of the virtual conductor after mapping the professors, understandability of the commands given to the students, students’ performance in the tasks and the threshold above which the software was recognising moves of an individual as correct. Described software is constantly being developed and adapted to meet the needs of a new user, which may give future opportunities to use it also for other educational or non-educational purposes.